Former male elite athletes have lower incidence of fragility fractures than expected - Tveit, M.; Rosengren, B. E.; Nyquist, F.; Nilsson, J.-A.; Karlsson, M. K. (Medicine & Science in Sports & Exercise, 2013)
Purpose: Physical activity during growth is associated with high peak bone mass and may, as a result, prevent osteoporosis later in life. It is therefore possible that athletic activity during youth could lower the risk of fragility fractures in old age. Although this is currently unclear and based on evaluations of surrogate skeletal end point variables in former athletes, we hypothesized that this is not the case.